Análise dos direcionadores de competitividade para a cadeia produtiva de biodiesel: o caso da mamona - César, Aldara da Silva (2009)
Biodiesel has been receiving great attention in Brazil. A federal program called National Program for Production and Use of Biodiesel (PNPB) and its corresponding legislation have created a huge demand for biodiesel. Furthermore, the PNPB began to stimulate not only its production from various types of oil but also its social inclusion. For this reason, this federal program established a set of policies aiming to include family farmers in the biodiesel production process in a sustainable way. Despite the real and potential growth of the Brazilian biodiesel market, it is surrounded by many uncertainties, especially with regard to its sustainability and economic viability in long term. The PNPB is strongly based on social development through the inclusion of family farmers in projects integrated with biodiesel plants. Among the various oilseeds, castor bean was identified as the ideal one to promote social development in the northeast. However, although promising, the mechanisms of the federal program are still insufficient to promote effective participation of family farmers, which are in the margin of this segment. The castor oil is considered a noble product. It is more expensive than many types of oil in the international market, which makes its use as fuel impracticable. Moreover, it is difficult to make the castor biodiesel technology follow the standards required by the National Petrol Agency. Considering these aspects, there has been some tendency of biodiesel plants - which continue to foster productive systems with castor oil to act as an intermediary in the ricino oil productive chain. Many efforts have been directed to enhance the agreements between producers and biodiesel plants. However, research shows that companies are facing huge problems in implementing contracts with family farmers. This dissertation intends to advance in the identification and the discussion of these obstacles, in order to increase the competitiveness of the biodiesel agribusiness chain, based on castor oil projects in Brazil. This dissertation describes and analyzes the functioning dynamics of this agroproduction chain, identifying the stakeholders who participate directly and indirectly of this chain. A competitiveness analysis model is proposed for the biodiesel production chain, and it is used to assess the competitiveness of agribusiness chain, mainly considering the bonds between industrial and agricultural production.